Tyrosine phosphorylation / dephosphorylation balance is involved in thrombin-evoked microtubular reorganisation in human platelets - Bouaziz, Aicha; Amor, Nidhal Ben; Woodard, Geoffrey E.; Zibidi, Hanen; López, José J.; Bartegi, Ahgleb; Salido, Ginés M.; Rosado, Juan A. (Thrombosis and Haemostasis, 2007)
We have investigated the intracellular mechanisms involved in microtubular remodelling by thrombin and its possible involvement in platelet aggregation and secretion. Platelet stimulation with thrombin induces a time- and concentration-dependent regulation of the microtubular content, which was found to be maximally effective at the concentration 0.1 U/ml. Thrombin (0.1 U/ml) evoked an initial decrease in the microtubule content detectable at 5 seconds (sec) and reached a minimum 10 sec after stimulation.The microtubular content then increased, exceeding basal levels again approximately 30 sec after stimulation. Inhibition of tyrosine phosphatases using vanadate abolished thrombin-induced microtubular depolymerisation while inhibition of tyrosine kinases by methyl-2,5-dihydroxycinnamate prevented microtubule polymerisation.Thrombin activates the cytosolic Brutons tyrosine kinase (Btk) and Src proteins. Inhibition of Btk or Src by LFM-A13 or PP1, respectively, abolished thrombin-induced microtubular polymerisation, while maintaining intact its ability to induce initial depolymerisation. Microtubular disruption by colchicine significantly reduced thrombin induced platelet aggregation and ATP secretion. Similar results were observed after inhibition of microtubular disassembly by paclitaxel.These findings indicate that thrombin induces microtubular remodelling by modifying the balance between protein tyrosine phosphorylation and dephosphorylation. The former seems to be required for microtubular polymerisation, while tyrosine dephosphorylation is required for microtubular depolymerisation. Both, initial microtubular disassembly and subsequent polymerisation are required for thrombin-induced platelet aggregation and secretion in human platelets.
Keywords: Thrombin; microtubules; aggregation; platelets; pp60src; Btk; protein kinases; protein phosphatases; ATP